The Philippines’ acquiescent ascension - Putra, Bama Andika (Frontiers in Political Science, 2024)
One of the puzzles to the Philippines’ middle power status is how it responds to great power rivalries in the Indo-Pacific. As a claimant state to the South China Sea, its responses in the maritime domain could reveal unique foreign policy patterns on how middle powers respond to overlapping maritime borders. However, the middle power literature cannot make sense of the inconsistencies in the Philippines’ foreign policy vis-à-vis the South China Sea, showcasing deference and defiance policies between 2016 and 2023. This study argues that bridging role theory into middle power literature can retrieve a more nuanced understanding of how middle powers behave. Utilizing primary and secondary data, this qualitative inquiry captures state narratives of the Philippines’ role conceptions and concludes: (1) Duterte’s abandonment of the US alliance and appeasement to China as ‘active independent’ and ‘anti-imperialist agent’ role conceptions; and (2) Marcos’s alignment to the US regional order, sea-based power projections, and leverage of the Philippines’ arbitral ruling representing ‘faithful ally’ and ‘example’ role conceptions. Bridging role theory in assessing maritime diplomatic actions allows for a nuanced understanding of why foreign policy inconsistencies occur.